Characterization of Optical Fibre Filters - Lam, Kwok Wah Dennis (My University, 1980)
The major purpose of the work described in this thesis is to characterize the basic properties and evaluate the potential of optical fibre filters. As it turns out, these filters have a spectral bandwidth in reflection which can be varied over a very wide range, from as narrow as 0.01 to several angstroms (A). As a result, they are potentially very important for applications as multiplexers and demultiplexers in Wavelength-Division-Multiplexing (WDM) in Optical Communication Systems (OCS) (WDM is a means of increasing the data handling capability of a given fibre system through the use of multiple propagating wavelengths). Up to the present moment, gratings in the form of slabs have invariably been employed as the multiplexers and demultiplexers in WDM which greatly restricts the number of wavelengths which can be used since a large spectral bandwidth separation (>100 Ǻ) is required between adjacent channels is such systems.
The optical fibre filters we report here can have a spectral bandwidth narrower than 1 Ǻ and consequently, employing them as multiplexers and demultiplexers in WDM allows a lot more channels to be transmitted. Other than this particular application, optical fibre filters can equally well function as resonant reflectors in a laser cavity, distributed feedback devices. tunable filters or external wavelength selective reflectors for heterojunction injection laser by end butting them to the latter. Furthermore, they have the potential to be used for equalizing material dispersion in OCS employing single mode fibres. Lastly, they can be tailored to give multifilters, comb filters or in general, filters that perform a variety of specified functions.
The approach to the characterization of optical fibre filters is divided into two parts. The first part deals with the development of a theoretical model that can be used to predict and describe the performance of the optical fibre filters. The second part describes the experiments for the actual fabrication of the filters and subsequent extraction of some of their physical parameters. By comparing the theory with the experimental results, we are able to deduce the range of filters available when using an Argon Iaser as the means of writing filters and subsequently evaluate their full potential in OCS. Also, a very important relationship between the optical writing power applied to a fibre and the resultant index perturbation in the fibre or equivalently, the resultant filter characteristics, is established so that the actual fabrication of filers designed to satisfy specific function can be performed.
Keywords: Electrical and Electronics; Electrical and Electronics